The Corrosion Behavior of Sputter-deposited Ternary Zr-(12-18)Cr-W Alloys in 12 M HCl Solution - Bhattarai, Jagadeesh (Journal of Nepal Chemical Society, 2010)
Ternary amorphous or/and nanocrystalline Zr-(12–18)Cr–W alloys were successfully prepared by direct current (DC) magnetron sputtering. The corrosion rates of Zr-(12- 18)Cr-W alloys are in the range of 1-2 x 10-3 mm/y which are even lower than those of the sputter-deposited binary W-Zr and W-Cr alloys, and are nearly one order of magnitude lower corrosion rate than those of the alloy-constituting elements in 12 M HCl at 30°C, open to air. All the examined sputter-deposited amorphous or/and nanocrystalline Zr-(12- 18)Cr–W alloys are passivated spontaneously. The zirconium addition suppresses the anodic dissolution current, and hence the anodic current densities of the alloys decreased with increasing the zirconium content in the alloys. It is, therefore, considered that the simultaneous additions of zirconium and tungsten with 12-18 at% of chromium enhance synergistically the corrosion-resistant and pitting corrosion of the sputter-deposited Zr-(12-18)Cr-W alloys in 12 M HCl. Keywords: Corrosion-resistant; Zr-Cr-W alloys; Electrochemical measurement; Pitting corrosion DOI: 10.3126/jncs.v26i0.3625 Journal of Nepal Chemical Society Vol. 26, 2010 Page: 13-21